The Discursive Dilemma in Monetary Policy - Carl Andreas Claussen; Øistein Røisland (Norges Bank, 2010)
The discursive dilemma implies that the policy decision of a board of policymakers depends on whether the board reaches the decision by voting directly on policy (conclusion-based procedure), or by voting on the premises for the decision (premise-based procedure). We derive results showing when the discursive dilemma may occur, both in a general model and in a standard monetary policy model. When the board aggregates by majority voting, a discursive dilemma can occur if either (i) the relationship between the premise and the decision is non-monotonic, or (ii) if the board members have different judgments on at least two of the premises. Normatively, a premise-based procedure tends to give better decisions when there is disagreement on parameters of the model.
hdl:11250/2497458
Keywords: 330